2005
DOI: 10.1007/s10616-005-3763-6
|View full text |Cite
|
Sign up to set email alerts
|

PLCγ2 Activates CREB-dependent Transcription in PC12 Cells Through Phosphorylation of CREB at Serine 133

Abstract: The cAMP and Ca 2+ signaling pathways activate the transcription factor CREB through its phosphorylation at Serine 133. Activation of CREB is involved in the regulation of various biological phenomena. To understand further the mechanisms of the regulation of CREB activity in response to activation of the cAMP and Ca 2+ signaling pathways, we examined the roles of PLCcs in CREB activation in PC12 cells. siRNA-mediated reduction of the expression of PLCc2, but not PLCc1, inhibited both the phosphorylation of CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Regulatory pathways that modulate bone metabolism are, therefore, likely to be key in determining whether cancer cells can home to the bone and establish metastatic lesions. In support of this idea, de novo production of L-serine, an essential factor for differentiation of mesenchymal bone marrow precursors into osteoclasts (Iwamoto et al, 2005), has been observed in osteotropic breast cancer cells (Pollari et al, 2011) (Figure 4). Specifically, expression of the three enzymes required for de novo serine synthesis, phosphoglycerate dehydrogenase (PHGDH), phosphoserine aminotransferase 1 (PSAT1), and phosphoserine phosphatase (PSPH), as well as the serine transporter SLC1A4, was observed to be significantly higher in bone-metastatic variants of breast tumors (Pollari et al, 2011).…”
Section: Bone Metastases: Undercover Agents To Destroy and Invade Bonementioning
confidence: 69%
“…Regulatory pathways that modulate bone metabolism are, therefore, likely to be key in determining whether cancer cells can home to the bone and establish metastatic lesions. In support of this idea, de novo production of L-serine, an essential factor for differentiation of mesenchymal bone marrow precursors into osteoclasts (Iwamoto et al, 2005), has been observed in osteotropic breast cancer cells (Pollari et al, 2011) (Figure 4). Specifically, expression of the three enzymes required for de novo serine synthesis, phosphoglycerate dehydrogenase (PHGDH), phosphoserine aminotransferase 1 (PSAT1), and phosphoserine phosphatase (PSPH), as well as the serine transporter SLC1A4, was observed to be significantly higher in bone-metastatic variants of breast tumors (Pollari et al, 2011).…”
Section: Bone Metastases: Undercover Agents To Destroy and Invade Bonementioning
confidence: 69%
“…The GAL4-dependent luciferase reporter plasmid (pGAL4RE-Luc) was generated as described previously (Iwamoto et al 2005). The ␤-galactosidase expression plasmid (pCMV-␤-gal) and PKA catalytic subunit expression plasmid (pCMV-PKA) were purchased from Clontech or Stratagene, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…COS-1 and PC12 cells were maintained and transiently transfected as described previously (Hosoda et al, 2004(Hosoda et al, , 2009Iwamoto et al, 2005). Luciferase and ␤-galactosidase activities were measured as described previously (Hosoda et al, 2004(Hosoda et al, , 2009Iwamoto et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…As described previously [38,39], cultured cells were maintained at 37°C in 95% O 2 5% CO 2 in Dulbecco’s modified Eagle’s medium (DMEM, NISSUI) supplemented with penicillin (100 U/ml) streptomycin (100 mg/ml) and 5% (HeLa cells and COS-1 cells) or 10 % (SH-SY5Y cells) fetal bovine serum (FBS, JRH BIOSCIENCE), respectively, and transiently transfected. Similarly, rat brain cortical neurons (CAMBREX) were maintained in Neuro basal medium (Invitrogen) supplemented with Penicillin-Streptomycin Mixture (TaKaRa), 200 mM L-Glutamine and B27 Supplement (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%